Penanaman Paham Literasi Digital Dalam Pembelajaran Pendidikan Agama Islam - Suanto, Asep Bambang (Al Mufid, 2024)
Technological sophistication can cause a digital divide such as the spread of fake news, issues containing radicalism, and others. Technological sophistication has positive and negative impacts. This is a challenge that must be overcome. Instilling an understanding of digital literacy integrated into learning is the key to creating understanding for students. The purpose of holding this PkM is to provide reinforcement of the instillation of an understanding of digital literacy in Islamic Religious Education learning. Stages of the implementation method; 1). conducting interviews with Islamic Religious Education subject teachers to find problems. 2). coordination with the principal for permission to carry out activities, determine the schedule and participants. 3). Implementation of training activities on instilling an understanding of digital literacy in learning. 4). Evaluation of the implementation of activities by asking questions about understanding digital literacy for participants, then opening with a discussion session and conclusions. From the results of the implementation, the instillation of an understanding of digital literacy integrated into learning is considered very beneficial. Instilling digital literacy understanding in students in Islamic Religious Education learning is done by controlling the implementation of students' social media, providing motivation, utilizing digital platforms such as YouTube with content prepared by teachers, directing students in digital literacy through interaction to solve problems and think critically